Investigating low order harmonics of sinusoidal pulse width modulation with voltage closed loop control - Ali Hussein Al-Omari; Saif Al-Zubaidi (Institute of Advanced Engineering and Science, 2022)
This paper investigates the low order harmonics of a simplified approach to generate high quality sinusoidal pulse width modulation (SPWM) waveform produced by voltage source inverter (VSI). Programmable interface controllers (PIC) microcontroller was chosen to produce the signals in Real time with voltage feedback to control the puls width during direct current (DC) link voltage reduction. The research considered simplicity, durability, and reliability as conditions. The proposed technique was successfully passed one of the biggest challenges which is time criteria presence due to execution time of the feedback loop and the transient time required for power electronics switches to turn fully off and on, known as dead time. The proposed technique can be considered as practical, high feasibility according to economic point of view and its accuracy to the input variables. The pseudocode, algorithm, and flowchart for closed loop real time voltage control to produce SPWM system using microcontroller was explained, illustrated and verified. The desired objectives were accomplished to achieve system that is able to generate high quality real-time SPWM with closed loop control.